Gothic Romance and the Birth of the Neo-Gothic Direction in Culture - Khabibova Shakhnoza Ismatullayevna (International Journal on Integrated Education, 2022)
The article is devoted to the Neo-Gothic style in culture and art. The author analyzes Neo-Gothic literature: its genesis, genre features, aesthetic characteristics, influence on a modern culture.